A New Isolate of Pediococcus pentosaceus (SL001) With Antibacterial Activity Against Fish Pathogens and Potency in Facilitating the Immunity and Growth Performance of Grass Carps - Gong, Liang; He, Haocheng; Li, Dongjie; Cao, Lina; Khan, Tahir Ali; Li, Yanping; Pan, Lifei; Yan, Liang; Ding, Xuezhi; Sun, Yunjun; Zhang, Youming; Yi, Ganfeng; et al. (Frontiers in Microbiology, 2019)
Probiotic-feeding continues to be a promising strategy to control the bacterial pathogens in aquaculture. A new Pediococcus pentosaceus strain (SL001) was isolated from thousands of soil samples, which exhibited wide antimicrobial spectrum of against fish pathogens, involving Aeromonas hydrophila, Aeromonas veronii, Aeromonas sobria, Edwardsiella tarda, Lactococcus garvieae and Plesiomonas shigelloide. The challenge test against A. hydrophila showed that the survival rate of SL001-supplemented group was significantly higher than that of control group (P<0.05). Moreover, SL001 could stably colonize in gut of grass carp and increased mucus-secreting goblet cells and extended intestinal villi could be observed in SL001-supplemented group (P<0.05). Feeding with SL001 supplemented diet could significantly enhance the growth rate (P<0.05) and markedly affect gut microbiota structure of grass carps, resulting in reduced potential pathogens and increased potential probiotics. Furthermore, feeding grass carps with SL001 caused the up-regulated expression of insulin-like growth factor (IGF-1 and IGF-2) and down-regulated expression of myostatin (MSTN-1 and MSTN-2) (P<0.05), which probably also account for the increased growth rate of SL001-fed group. Meanwhile, relative mRNA expression levels of immune-related genes in liver, spleen and head kidney were analyzed in grass carps after feeding for 30 days with SL001 supplemented diets. In all three immune organs, the expression levels of immunoglobulin M (IgM) and complement 3 (C3) were significantly increased (P<0.05), whereas the interleukin-8 (IL-8) was down-regulated (P<0.05). Besides, whole genome sequencing revealed several probiotics properties of SL001, including organic acid synthesis, bacteriocin synthesis (coagulin), superoxide dismutase and digestive enzymes. In conclusion, P. pentosaceus SL001 which could enhance immunity and promoter growth rate of grass carps, is prospective to be used as a dietary probiotic in freshwater fish aquaculture.